2023
DOI: 10.1021/acs.jafc.3c01032
|View full text |Cite
|
Sign up to set email alerts
|

Plant Defensin-Dissimilar Thionin OsThi9 Alleviates Cadmium Toxicity in Rice Plants and Reduces Cadmium Accumulation in Rice Grains

Abstract: Thionins are important antibacterial peptides in plants. However, the roles of plant thionins, especially the defensindissimilar thionins, in alleviating heavy-metal toxicity and accumulation remain unclear. Here, cadmium (Cd)-related functions and mechanisms of the defensin-dissimilar rice thionin OsThi9 were investigated. OsThi9 was significantly upregulated in response to Cd exposure. OsThi9 was localized to the cell wall and was shown to bind Cd; these characters help to increase Cd tolerance. In Cdexposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Only a few papers have investigated the role of thionins in mitigating the toxicity of heavy metals to plants. Liu et al (2023) showed that the defensin-dissimilar thionin gene OsThi9 in rice was strongly expressed in roots, basal and middle stems, and growing seeds after exposure to 0.1 µM CdCl2 for up to 7 days [62]. Overexpression of OsThi9 in rice reduced the translocation of Cd from roots to shoots, thereby reducing Cd concentrations in the leaves, stems, and brown rice of the OsThi9-overexpressing plants grown in Cd-contaminated soil.…”
Section: Transgenic Plants With Thionin Genes For Enhanced Biotic And...mentioning
confidence: 99%
“…Only a few papers have investigated the role of thionins in mitigating the toxicity of heavy metals to plants. Liu et al (2023) showed that the defensin-dissimilar thionin gene OsThi9 in rice was strongly expressed in roots, basal and middle stems, and growing seeds after exposure to 0.1 µM CdCl2 for up to 7 days [62]. Overexpression of OsThi9 in rice reduced the translocation of Cd from roots to shoots, thereby reducing Cd concentrations in the leaves, stems, and brown rice of the OsThi9-overexpressing plants grown in Cd-contaminated soil.…”
Section: Transgenic Plants With Thionin Genes For Enhanced Biotic And...mentioning
confidence: 99%
“…Water and soil contamination has always been a noticeable matter in environmental studies, leading to the developing and designing heavy metal ions receptors [ [1] , [2] , [3] , [4] ]. Mercury is a highly toxic metal [ [5] , [6] , [7] ] and its compounds are used in various industries and present in wastewaters, which can accumulate in living organisms. Constant exposure to mercury can cause permanent damage to DNA besides disorders in the brain, kidney, lungs, stomatitis, and digestive system [ 8 , 9 ], as well as neurological problems and other severe diseases like acrodynia, Hunter-Russell, Minamata, and even death [ [10] , [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [ 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 ...…”
unclassified